2021
DOI: 10.3389/fpls.2021.776971
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Pattern of Aerenchyma Formation Using the Ti-Gompertz Model in Rice Adventitious Roots

Abstract: The longitudinal pattern of root aerenchyma formation of its relationship with the function of adventitious roots in rice remains unclear. In this study, the percentage of the aerenchyma area to the cross-sectional area (i.e., aerenchyma percentage) was fit with four non-linear models, namely, W0-Gompertz, Ti-Gompertz, logistic, and von Bertalanffy. Goodness-of-fit criteria such as the R2, the Akaike information criterion (AIC), and the Bayesian information criterion (BIC) were used to select the model. The bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…Previous studies reported that aerenchyma percentage varies substantially depending on the sampling location within the root (distance from the base or root) (Bouranis et al, 2006;Chen et al, 2021;Xu et al, 2013) but they did not investigate differences in aerenchyma levels observed between roots of the same individual. In this study, we observed a high intra-individual variation in this trait, demonstrated by large differences in percentage aerenchyma between two adventitious roots sampled per plant.…”
Section: Genetic Regulation Of Aerenchyma Formation In Barleymentioning
confidence: 99%
“…Previous studies reported that aerenchyma percentage varies substantially depending on the sampling location within the root (distance from the base or root) (Bouranis et al, 2006;Chen et al, 2021;Xu et al, 2013) but they did not investigate differences in aerenchyma levels observed between roots of the same individual. In this study, we observed a high intra-individual variation in this trait, demonstrated by large differences in percentage aerenchyma between two adventitious roots sampled per plant.…”
Section: Genetic Regulation Of Aerenchyma Formation In Barleymentioning
confidence: 99%